Comparative Analysis of Bid Pricing Strategies in E-Procurement Ship Docking Tenders in Indonesia Using the Friedman and Gates Models - Maulana Fariz Baharudin; Fitri Hardiyanti; Aditya Maharani (JOURNAL OF SOCIETY INNOVATION AND DEVELOPMENT, 2026)
Indonesia's shipbuilding sector has significant maritime potential; yet escalating rivalry in ship docking tenders necessitates that contractors establish bid prices sufficiently low to get contracts while still ensuring a satisfactory profit margin. Research Objective: This research seeks to compute and evaluate optimal markup values and anticipated profits using the Friedman and Gates bid price strategy models to determine the best competitive model for e-procurement ship docking tenders in Indonesia. The study employs quantitative comparison analysis with finalized ship docking tender data from the LPSE Ministry of Transportation database for the years 2021 to 2023. Methodology: Following the application of selection criteria, the research examined 22 ship docking tender samples from 27 shipyard contractors, using single-normal and multi-normal distribution methods to estimate winning probabilities, optimal markups, and expected profits. Key Findings: The findings indicate that the Friedman model utilizing a multi-normal distribution yields the lowest optimal markup values, between 5% and 20%. In contrast, the Friedman single-normal distribution results in 12% to 13%, the Gates multi-normal distribution ranges from 6% to 20%, and the Gates single-normal distribution consistently maintains a value of 17%. Key Findings: Consequently, the Friedman model with a multi-normal distribution is recognized as the optimal bidding method for enhancing the likelihood of winning bids by offering a more competitive bid price. The results suggest that shipyard contractors may use past tender data and bidding models to achieve a balance between competitiveness and profitability, mitigate price uncertainty, and enhance strategic decision-making in public ship docking bids.